The Federal Democratic Republic of Ethiopia : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The Federal Democratic Republic of Ethiopia. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Ethiopia's recent macroeconomic performance has continued to be strong overall, although with some rising domestic and external vulnerabilities. Economic growth in 2014/15 was buoyant, supported by booming manufacturing and construction sectors. However, inflation has been on the rise, with domestic food prices pushing it above 10 percent. External vulnerabilities have also increased as exports of goods and services slowed significantly, while imports continued growing fast. In the medium term, the IMF staff forecast strong growth at 7.5-8 percent. Public investment is expected to moderate, while private investment is projected to increase only gradually.